HUBUNGAN DUKUNGAN KELUARGA DENGAN PENERIMAAN DIRI WARGA BINAAN LEMBAGA PEMASYARAKATAN PEREMPUAN KELAS IIA SUNGGUMINASA KABUPATEN GOWA - Damayarti, Ledy; Gaffar, Syamsul Bakhri; Asri, Muhammad (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2024)
This research is a quantitative study using a descriptive method that aims to describe family support, the level of self-acceptance of inmates and the relationship of family support to self-acceptance of inmates at Class IIA Sungguminasa Women's Penitentiary, Gowa Regency. The independent variable in this study is family support, while the dependent variable in this study is self-acceptance. The population in this study were all inmates at the Class IIA Sungguminasa Women's Correctional Institution, Gowa Regency, totaling 367 people, while the sample in this study were 65 people with a random sampling technique. The data analysis technique used is simple linear regression analysis. Based on the results of the descriptive analysis, it was obtained an overview of family support for each indicator of variable support, namely informative assistance indicators 93%, emotional attention 94%, instrumental assistance 70%, and assessment assistance 92%. The family fraction is classified as moderate with a proportion of 34% and self-acceptance is classified as moderate with a proportion of 32%. There is a significant relationship between family support and the acceptance of inmates at the Class IIA Sungguminasa Women's Penitentiary, Gowa Regency. With a pearson product moment correlation coefficient of 0.550 which is included in the medium category.